Effects of glycerin oil and lavender oil massages on hemodialysis patients' restless legs syndrome. Issue 1 (January 2020) - Mirbagher Ajorpaz, Neda; Rahemi, Zahra; Aghajani, Mohammad; Hashemi, Sayyed Hossein
Abstract: Objectives: To determine the effects of glycerin oil and lavender oil massages on hemodialysis patients' restless legs syndrome (RLS). Methods: Ninety hemodialysis patients with RLS were randomly allocated into two intervention groups and one control group, each consisting of 35 participants. The control group received routine care, and the intervention groups received effleurage massage with lavender and glycerin oil in addition to routine care for one month. RLS intensity was measured among the three groups using the Restless Legs Syndrome Rating Scale. Results: At the beginning of the study, the results showed no significant difference among the three groups' scores. At the end of the study, the mean RLS scores were significantly lower in the intervention groups compared to the control group ( F  = 63.4, p  ≤ 0.001). This difference was not significant between the two intervention groups; nonetheless, the differences between the control and lavender oil groups, as well as the control and glycerin oil groups, were significant ( p  < 0.05). Conclusion: The findings showed the effectiveness of the oils through the effleurage massage for reducing RLS in a sample of hemodialysis patients.